INPLEMENTASI BUSINESS INTELLIGENCE DAN MARKET BASKET ANALYSIS UNTUK ANALISA DATA PENJULAN DI PT. ABC - I Putu Susila Handika; I Gusti Agung Ayu Ari Satyawati (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
In the midst of the outbreak of the Covid-19 pandemic in 2020 in Indonesia, there was a change in the tendency of customer behavior to process shopping transactions, especially at minimarket outlets. With the implementation of physical distancing, customers are required to shop as effectively as possible to avoid accumulation in outlets. Company management must make a strategy to respond to changes in customer behavior. In this study, Business Intelligence and Market Basket Analysis methods were developed, namely Apriori to analyze customer behavior by analyzing sales transaction history. The results show that the Business Intelligence dashboard can display data in the form of graphs and tables, making it easier for users in the analysis process. In addition, the Association Rule using the Apriori method produces support and confidence values ​​as a description of interrelated products, so that merchandising parties can easily make decisions. The results of the blackbox test show that the application developed can be accepted by the user because all user needs can be completed by the application